The Influence of Organizational Culture on Organizational Commitment and Job Satisfaction to Improve the Officer Performance Assigned In Boven Digoel Regency - Martinus Kirimanop; Cepi Pahlevi; Fauziah Umar; Bintang Balele (Magister Management, Hasanuddin University, 2020)
The research objective is to analyse the effect of organizational culture on employee performance with the mediation of the variable organizational commitment and job satisfaction. Data analysis in this research is quantitative using a path analysis model (Path) with the help of Smart PLS Software version 3.2 .8. The results found that organizational culture had a positive and significant effect on organizational commitment and job satisfaction. Interestingly, it indicates an insignificant effect on employee performance. Organizational commitment and job satisfaction both show a significant positive effect on employee performance. For testing the indirect effect is found empirical facts that organizational culture has a significant positive effect on employee performance if mediated by organizational commitment. The organizational culture does not have a significant positive effect on employee performance if mediated by job satisfaction.